Potential net clinical benefit of population-wide implementation of apixaban and dabigatran among European patients with atrial fibrillation - Pisters, Ron; Nieuwlaat, Robby; Lane, Deirdre A.; Crijns, Harry J. G. M.; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2013)
Vitamin K antagonists (e.g. warfarin) are commonly underutilised, due to limitations such as the need for monitoring, in high-risk atrial fibrillation (AF) patients. We therefore aimed to model the potential impact on clinical outcomes in patients with AF with the use of the novel oral anticoagulant (OAC) drugs, apixaban and dabigatran. We identified all high-risk (CHA2DS2-VASc score ≥2) patients with non-valvular AF and known one-year follow-up from the EuroHeart Survey on AF (EHS-AF). We modelled the expected numbers of clinical events on the novel OACs using published hazard ratios from their respective phase 3 clinical trials and calculated the numbers needed to treat and the mathematical net clinical benefit. Our analysis included 3,400 patients [39% females; mean (SD) age 67 (12) years; CHA2DS2-VASc score 3.0 (1.8)] of which 330 were excluded from the modelling analysis due to concomitant use of OAC and antiplatelet drugs. During one-year follow- up, 108 (3.2%) patients experienced thromboembolism, 51 (1.5%) major bleeds and 146 (4.3%) died. Compared to current treatments (i.e. warfarin, aspirin or nothing) the use of apixaban in highrisk patients would have potentially prevented an additional 17 deaths, 27 strokes and eight major bleeds within this cohort. With use of dabigatran 150 mg BID, 34 strokes could have been prevented and for dabigatran110 mg BID, 16 strokes and six major bleeds would be avoided. Extrapolation of the data from the EHS-AF to the whole of Europe would translate into the prevention of an additional 64,573 major cardiovascular events and deaths each year among patients with a CHA2DS2-VASc ≥2, by the use of apixaban, 43,235 with the use of dabigatran 150 mg bid and 27,272 with the use of dabigatran 110 mg bid. In conclusion, based on this modelling exercise, the utilisation of apixaban and dabigatran for thromboprophylaxis could provide a profound annual mathematical net clinical benefit on stroke and major bleeds, in European AF patients.Note: The editorial process for this paper was fully handled by Prof. C. Weber, Editor in Chief.
Keywords: Atrial fibrillation; oral anticoagulation; stroke prevention